Kriteria Desain Perancangan Wisata Di Kawasan Bendungan Gerokgak, Kabupaten Buleleng, Bali - Ni Made Prita Ayuningtyas Ayuningtyas; I Gede Surya Darmawan; I Wayan Wirya Sastrawan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
Gerokgak Dam has the potential to be developed into a tourist area based on the Buleleng Regency Perda which regulates the RTRW which is discussed in regulation No. 9 of 2013. The main function of the Gerokgak dam is to irrigate rice fields and plantations during the dry season. Over time, the tourism sector began to grow naturally. Gerokgak Dam has natural potential, cultivation, and water tourism. However, the land use pattern in the Gerokgak dam area does not yet have a zoning system so that there is no division of tourist activity zones that meet the requirements both in terms of architecture and security. This is related to efforts to reduce disaster risk in dam tourism areas. The purpose of this design is to design a tourist facility for the Gerokgak dam that meets the requirements in terms of comfort, safety, and architecture. This design uses an environmental approach with a design concept, namely the connectivity of nature and buildings, realized with the theme of eco-architecture. Data collection methods in the form of literature studies, field observations, interviews and data presentation methods, namely data compilation and classification. The results of the research are the segmentation of the area into several zones that consider the level of risk & area characteristics, namely: the supporting zone (green zone), and the main zone (built zone). The design design criteria include aspects of safety, security, comfort, and beauty, so that land use in the Gerokgak dam area takes into account these limiting factors.